The Effects of Ritodrine and Ritodrine-Indomethacin Combination on Spontaneous Contractions of Myometrium Isolated From Pregnant Rats in Which Preterm Labour was Induced by Lipopolysaccharide Administration - Çelik, Hüsnü; Ayar, Ahmet; Kalkan, Ahmet; Çebi, Kibar (Fırat University, 2001)
The aim of this study was to determine and compare the efficiency of ritodrine and ritodrine-indomethacin combination on spontaneous contractions of myometrium isolated from pregnant rats which presents Lipopolysaccharide (LPS)-induced preterm labour model. 50µ.g/kg LPS (Escherichia coli, serotype 055:B5, Sigma) was intraperitonealy injected and myometrium samples obtained after servical dislocation and isometric contractions were evaluated. Results were statistically analysed using Wilcoxon Rank, Kruskal-Wallis Analysis of Variance and Mann Whitney U tests. Application of 10-8 g/ml ritodrine inhibited the amplitude and frequency of spontaneous contractions of myometrium isolated from normal pregnant rats by 96.6% and 69.8%, respectively CP

Bu çalışmanın amacı lipopolisakkarit (LPS) ile preterm eylem oluşturulan gebe radardan izole edilen miyometriyum kesitlerinde spontan kontraksiyonlar üzerine ritodrin ve ritodrin-indometazin kombinasyonunun etkinliğini belirleyerek karşılaştırmaktır. Bu amaçla, gebe sıçanlara 50µg/kg intraperitoneal LPS (Escherichia coli, serotype 055:B5, Sigma ) enjekte edilerek preterm eylem oluşturuldu ve servikal dislokasyonla sakrifiye edilerek alınan miyometriyum kesitleri asılarak izometrik kasılmalar değerlendirildi. İstatistiksel yöntem olarak Wilcoxon Rank testi, Kruskal-Wallis varyans analizi ve Mann Whitney U testleri kullanıldı. 10-8g/ml ritodrin normal gebe sıçanlardan izole edilen miyometriyum kesitlerinde spontan konfeksiyonların amplitütlerinde %96.6, frekansında %69.8 oranında inhibisyona neden oldu (p
LİPOPOLİSAKKARİT İLE PRETERM EYLEM OLUŞTURULAN GEBE RATLARDAN İZOLE EDİLEN MİYOMETRİYUMDA SPONTAN KONTRAKSİYONLAR ÜZERİNE RİTODRİN, RİTODRİN+İNDOMETAZİN KOMBİNASYONUNUN ETKİLERİ